Shalat Tarawih Juziyyah in Madrasah Huffadz: Community of Memorizers of Quran, Identity Politics, and Religious Authority - Waffada Arief Najiyya (UIN Sunan Kalijaga Yogyakarta, 2018)
This article delves the reception of the Quran in Indonesia. This article, phenomenologically speaking, explores the tradition of tarawih juziyyah (the tarawih with completion of Quranic recitation) during Ramadan in Pondok Pesantren Madrasah Huffadz Krapyak Yogyakarta. This paper focuses on hierarchy of meanings emerging from the research subjects involved in the tradition. In addition to that, this research elaborates the transmission and transformation of the Quran taking place in ritual and non-ritual dimension of the tradition. Furthermore, it seeks out the hegemony and identity negotiation being hidden in the tarawih. Concluding the research, I argue that the tarawih juziyyah encapsulates two phenomena (prayer and khataman) in one tradition and thus proves that the Quran holds sufficient power with which its memorizer gain, after sorts of politicization, highly prestigious status among muslims community.[Penelitian ini membahas tentang bentuk tradisi resepsi al-quran di Indonesia. Penelitian ini secara fenomenologis akan mengeksplor praktek shalat tarawih juziyyah (shalat tarawih dengan membaca satu setengah juz dari al-quran setip malamnya) pada bulan ramadlan di Pondok Pesantren Madrasah Huffadz Krapyak Yogyakarta. Fokus penelitian ini terletak pada hierarki makna yang muncul dari para subjek penelitian terkait dengan tradisi shalat tarawih juziyyah tersebut. Selain itu, penelitian ini melihat bentuk transmisi dan transformasi pengetahuan yang terjadi, menunjukkan adanya dimensi ritual dan non-ritual dalam praktek itu, serta menjelaskan adanya hegemoni dan negosiasi identitas yang muncul dari tradisi shalat tarawih juziyyah tersebut. Salat tarawih juziyah, yang mengapsulkan dua fenomena dalam satu praktek, menjadi bukti bahwa al-Qur ’an memiliki kuasa yang cukup besar untuk dipolitisasi sedemikian rupa sehingga penghafalnya mendapatkan status sangat prestis di kalangan masyarakat muslim.]